O interacionismo sociodiscursivo, o livro didático e a gramática - Carvalho, Ana Cláudia Garcia de (2013)
Verbal interaction is the fundamental reality of language and discourse is the way by which the subjects produce this interaction – a way of social production of language. Based on Mikhail Bakhtin’s (2006) reflections and discoveries and Jean-Paul Bronckart’s (2009) investigations about sociodiscoursive interactionism (SDI), this research studies how grammar is approached in the Portuguese language textbooks, from the 6th to the 9th grade. The following textbooks were examined: Português Linguagens, by William Roberto Cereja and Thereza Cochar Magalhães, and A Aventura da Linguagem, by Luiz Carlos Travaglia, Maura Alves de Freitas Rocha and Vânia Maria Bernardes Arruda Fernandes. As far as the methodology is concerned, this research considered its theoretical and investigative character and two stages of analysis were delimited. The first is the discussion of Bakhtin’s interactionism concepts and Bronckart’s sociodiscoursive interactionism concepts. The second is the discussion and analysis of the grammar work proposed by the textbooks. The rbesearch becomes relevant because, up to now, the failure of Portuguese language teaching as a first language in Brazilian schools has been testified. Moreover, it is justified by the difficulty that many teachers face in the teaching of grammar. This study aims at providing contribution to teachers’ pedagogical action based on sociodiscoursive interactionism for the teaching of the Portuguese language in which grammar is treated as a means to achieve mastery over language use, so that the teaching of the Portuguese language becomes more productive in terms of learning. As result of the analysis, we found that the textbook mediates specific student with the world, but that the teaching of the Portuguese language is also focused on teaching the metalinguistic activity and not the use of the language.